Induced Proprioceptor and Low-Threshold Mechanoreceptor Neurons Derived from Human Pluripotent Stem Cells Exhibit Distinct Functional Mechanosensory Properties - Hulme, Amy J.; Finol-Urdaneta, Rocio K.; McArthur, Jeffrey R.; Marzano, Nicholas R.; Maksour, Simon; Thind, Amarinder; Guo, Yang; Kaul, Dominic; Maddock, Marnie; Friedrich, Oliver; Martinac, Boris; Adams, David J.; et al. (Advanced Science, 2025)
Mechanosensory neurons are a specialized class of neurons that detect mechanical stimuli elicited by external or internal body forces. Two major subclasses of mechanosensory neurons reside within the dorsal root ganglia; proprioceptor neurons (PN) that innervate muscle tissue and low threshold mechanoreceptor neurons (LTMR) that innervate skin. To date, the specific cellular neurophysiology of PN and LTMR subclasses are primarily defined by animal models due to the limited availability of human neural tissue. Here an efficient approach is described for generating PN and LTMR from human pluripotent stem cells (hPSC) by inducing co-expression of NGN2/RUNX3 or NGN2/SHOX2 in hPSC-derived neural crest, respectively. Molecular and functional mechanosensory profiles are validated in both populations. Of significance, functional interrogation of induced mechanosensory subtypes reveals their distinct responses to mechanical stimuli. Induced proprioceptor neurons produce scaled responses to increasing mechanical stimuli that can sustain repetition and result in action potential firing. In contrast, induced LTMRs desensitize upon repeated mechanical stimuli and display a lower mechanical threshold for action potential firing. Furthermore, both subtypes predominantly rely on PIEZO2 for mechanosensory function. These findings highlight the unique mechanically sensitive profiles and excitability properties that may distinguish human mechanosensory subtypes, distinct from the presence of end-organs.
CRIS-Team Scopus Importer:2025-12-19
Keywords: dorsal root ganglia; human pluripotent stem cells; low threshold mechanoreceptor; mechanosensation; NEUROGENIN-2; PIEZO2; proprioceptor; sensory neuron